Application of ternary cementless hybrid binders for pervious concrete. (5th September 2022) - Lin, Kae-Long; Lin, Wei-Ting; Korniejenko, Kinga; Hsu, Hui-Mi
Highlights: A new cementless binder is developed from CFA, ggbs and DG. Innovative cementless mixtures can be used as a binder for pervious concrete. Reasonable amount of DG content can effectively improve the strength. Main hydration reactants of cementless binders are C-S-H and AFt crystals. Cementless pervious concrete has a compressive strength of 12 MPa. Abstract: In this study, alkali-free activator-type ternary cementless binders were developed using ground granulated blast-furnace slag (GGBS), co-fired fly ash (CFA), and desulfurization gypsum (DG). The properties of cementless binders were verified and used to investigate the feasibility of application to pervious concrete. The results indicated that including CFA in cementless binders increased the initial and final setting times. The addition of DG shortened the setting time and the addition exceeded 7 wt% resulting in a rapid setting, which did not meet the ASTM C150 specification. A binary cementless binder with a CFA-GGBS mix achieved a maximum compressive strength up to 54% of the cement group, and the optimum mixture was 70% GGBS with 30% CFA. DG increased the SO3 content of the binder and promoted the production of ettringite (AFt), resulting in an effective increase in compressive strength up to 92% of the cement group. The optimum proportion of cementless binders to meet the setting times was 70% GGBS, 25% CFFA, and 5% FGDG, resulting in maximum compressive strength up to 79% of the cement group. During the hardening period of the cementless pastes, the generation of AFt affected the internal pore structures of the C-S-H colloids, resulting in higher capillary pores. DG also accelerated the production of AFt, causing an increase in capillary pores. In addition, the maximum compressive strength of cementless pervious concrete developed in this study reached 12 MPa, and the permeability coefficient was up to 0.156 cm/s. It can meet the requirements of the general pervious pavement specification in Taiwan.